Evaluating The Implementation Of The Disability Law: A Case Study In The Faculty Of Education, Indonesia University Of Education - Atep Chairul Hikmat; Rahmat, Nabila; Nanda Cahyani; Rifa Sri Khasanah (Penerbit Hellow Pustaka, 2025)
This article evaluates the implementation of the Disability Law at Universitas Pendidikan Indonesia (UPI) with the aim of identifying successes and challenges in its execution. The study adopts a qualitative method, utilizing data collection through interviews, observations, and document analysis. The results indicate that while efforts have been made to meet the needs of students with disabilities, there are still obstacles regarding accessibility, understanding, and support in terms of facilities and human resources. These findings emphasize the need for increased awareness and training programs to better support students with disabilities in the academic environment. This article aims to provide recommendations for the development of more inclusive and sustainable policies at UPI and other educational institutions.